2001
DOI: 10.1081/bio-100001253
|View full text |Cite
|
Sign up to set email alerts
|

Vasoconstrictive Response of Rat Mesenteric Arterioles Following Infusion of Cross-Linked, Polymerized, and Conjugated Hemoglobin Solutions

Abstract: Infusion of hemoglobin-based oxygen-carrying solutions (HBOCs) produce an immediate rise in blood pressure with most solutions, both in animals and humans, as a result of systemic and pulmonary vasoconstriction. Autoregulation of the O2 supply by the microvasculature has been proposed as a phenomenon involved in the vasoconstriction elicited by HBOCs. Nevertheless, little is known about the ability of various HBOCs to induce constriction in the microcirculation according to their specific physicochemical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
(25 reference statements)
0
14
0
1
Order By: Relevance
“…There have been considerable discussions on the reasons why infusion of most hemoglobin-based blood substitutes result in increased vasoactivity whereas a few others do not [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. One proposal is that the tetrameric hemoglobin component transverses the intercellular junction of the endothelial cell lining and binds nitric oxide from the interstitial space needed for normal vasodilatation [3][4][5]9,10,14].…”
Section: Introductionmentioning
confidence: 99%
“…There have been considerable discussions on the reasons why infusion of most hemoglobin-based blood substitutes result in increased vasoactivity whereas a few others do not [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. One proposal is that the tetrameric hemoglobin component transverses the intercellular junction of the endothelial cell lining and binds nitric oxide from the interstitial space needed for normal vasodilatation [3][4][5]9,10,14].…”
Section: Introductionmentioning
confidence: 99%
“…The system that bonds bovine Hb may result in problems of antigenicity on repeated usage [9]. Other conjugated Hbs like, dextran-benzene-tetracarboxylate-conjugated Hb (Hb-Dex-BTC), is undergoing animal trials [10].…”
Section: Polymer Conjugated Haemoglobinmentioning
confidence: 99%
“…Phase I trial studies conducted by Baxter in 1992 have revealed considerable success, excepting a dose-related elevation of blood pressure and decline in heart rate, corresponding to maximum dosage of 0.1 gm/Kg [1]. O'Hara et al observed an increase in whole blood methaemoglobin fraction (0.84 +/-0.77% at baseline to 4.08 +/-1.36%) during 48 hours of the DCL Hb infusion (dosage :936 +/-276 mg/Kg), but it did not reach a range associated with complications [10][11][12].…”
Section: Intramolecular Cross-linked Haemoglobinmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers found that some hemoglobin-based oxygen carriers caused transient systemic hypertension [78,79] and reduced cardiac output [80]. This is because large infusions of blood substitutes lower blood viscosity and the shear stress on the endothelium, which down-regulates the production of vasodilators by endothelial cells, causing vasoconstriction and increasing total peripheral vascular resistance [81]. In the hemorrhagic shock model, viscous blood substitutes limit vasoconstriction [82,83] and improve functional capillary density and oxygen content.…”
Section: Treatments That Increase Blood Viscositymentioning
confidence: 99%